Buffering Capacity and Effects of Sodium Hexametaphosphate Nanoparticles and Fluoride on the Inorganic Components of Cariogenic-Related Biofilms In Vitro - Caio Sampaio; Alberto Carlos Botazzo Delbem; Thayse Yumi Hosida; Ana Vitória Pereira Fernandes; Guilherme dos Santos Gomes Alves; José Antônio Santos Souza; Douglas Roberto Monteiro; Juliano Pelim Pessan (MDPI AG, 2022)
Despite the remarkable effects of sodium hexametaphosphate nanoparticles (HMPnano) on dental enamel de-/re-mineralization processes, information on the effects of these nanoparticles on biofilms is scarce. This study assessed the effects of HMPnano, with or without fluoride (F), on the inorganic components and pH of Streptococcus mutans and Candida albicans dual-species biofilms. Solutions containing conventional/micro-sized HMP (HMPmicro) or HMPnano were prepared at 0.5% and 1%, with or without 1100 ppm F. A 1100 ppm F solution and pure artificial saliva were tested as positive and negative controls, respectively. The biofilms were treated three times and had their pH analyzed, and the concentrations of F, calcium, phosphorus, and HMP in the biofilm biomass and fluid were determined. In another set of experiments, after the last treatment, the biofilms were exposed to a 20% sucrose solution, and the biofilm pH and inorganic components were evaluated. The 1% HMPnano solution with F led to the highest biofilm pH, even after exposure to sucrose. The 1% HMPnano solution without F led to significantly higher phosphorus concentrations in comparison to all other groups. It can be concluded that 1% HMPnano and F influenced the biofilm pH, besides affecting most of the inorganic components of the dual-species biofilms.